C37.90.2-2024 - IEEE Standard for Relays, Relay Systems, and Control Devices used for Protection and Control of Electric Power Apparatus--Radiated Electromagnetic Interference Withstand Capability Requirements and Tests (IEEE, 2025)
Design tests for relays and relay systems that relate to the immunity of this equipment to radiated electromagnetic interference from transceivers are specified in this standard. Field strength, test frequencies, modulation, sweep rates, equipment setup and connection, test procedures, criteria for acceptance, and documentation for test results are described. This standard has been harmonized with IEC standards where consensus could be reached.
Keywords: Electromagnetic interference.